2006
DOI: 10.1042/cs20050178
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte apoptosis in the pathogenesis and resolution of lung disease

Abstract: Apoptosis, programmed cell death, of neutrophil and eosinophil granulocytes is a potential control point in the physiological resolution of innate immune responses. There is also increasing evidence that cellular processes of apoptosis can be dysregulated by pathogens as a mechanism of immune evasion and that delayed apoptosis, resulting in prolonged inflammatory cell survival, is important in persistence of tissue inflammation. The identification of cell-type specific pathways to apoptosis may allow the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 164 publications
(157 reference statements)
2
45
0
Order By: Relevance
“…Our observation suggests occurrence of non-caspasedependent induction of apoptosis, which would be in agreement with the observed intermediate level of BAL PMNs in R-roscovitine + zVAD-fmk cotreatment. Few annexin V + 7-AAD + cells were measured, which could be because of either the experimental procedures or the phagocytosis (for example, by macrophages), since extracellular membrane PS targets cells for phagocytosis (13). To expand our data on R-roscovitine effects on LTA-induced pulmonary inflammation, we determined the impact of R-roscovitine on a progressing inflammatory response in the lung elicited by the clinically relevant gram-positive pathogen S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation suggests occurrence of non-caspasedependent induction of apoptosis, which would be in agreement with the observed intermediate level of BAL PMNs in R-roscovitine + zVAD-fmk cotreatment. Few annexin V + 7-AAD + cells were measured, which could be because of either the experimental procedures or the phagocytosis (for example, by macrophages), since extracellular membrane PS targets cells for phagocytosis (13). To expand our data on R-roscovitine effects on LTA-induced pulmonary inflammation, we determined the impact of R-roscovitine on a progressing inflammatory response in the lung elicited by the clinically relevant gram-positive pathogen S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…PMNs contain and generate toxic substances that are harmful to the lung when they exocytose their granules and/or undergo uncontrolled necrosis. Therefore, successful resolution of infection entails removal of excess cellular infiltrate (11,13). Herein, apoptosis is a strong regulatory mechanism during lung inflammation (14): phagocytosis of apoptotic PMNs by macrophages reprograms macrophages to release antiinflammatory mediators, thus aiding resolution of (harmful) inflammation (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3 (Cas3) is the critical executioner of apoptosis, and granulocytes are susceptible to apoptosis. 37 Hypermorphic expression of…”
Section: Resultsmentioning
confidence: 99%
“…[3,5] Apoptosis is characterized by specific morphological and biochemical changes such as cell shrinkage, nuclear coalescence, chromatin condensation and endonuclease-catalyzed DNA breakdown followed by fragmentation of the cell into apoptotic bodies, which are phagocytozed intact without further induction of inflammation. [6,7] Apoptosis and its induction is regarded as an important mechanism in the resolution of eosinophilic inflammation [3,5,6] and it has been shown that eosinophil apoptosis is delayed in patients with asthma, inhalant allergy and atopic dermatitis [8,9]. In vitro, eosinophil apoptosis is inhibited by cytokines such as interleukin (IL) -3, IL-5 and granulocyte/macrophage colony-stimulating factor.…”
Section: Introductionmentioning
confidence: 99%